2,5-Bis[2-(2-methoxyethoxy)phenyl]-1,3,4-oxadiazole - Tian, Xia (International Union of Crystallography, 2009)
In the title compound, C(20)H(22)N(2)O(5), the central 1,3,4-oxadiazole ring is essentially planar [r.m.s. deviation from the best plane of 0.0011 Å] and makes dihedral angles of 4.10 (3) and 13.32 (4)° with the two benzene rings. In the crystal structure, the packing is stabilized by weak non-classical intermolecular C—H⋯N hydrogen bonds, which link the molecules into an extended network.